Cr/Sc Multilayer Radiator for Parametric EUV Radiation in "Water-Window" Range; RREPS-15. Radiation from Relativistic Electrons in Periodic Structures - Uglov S. R. Sergey Romanovich; Kaplin V. V. Valeriy Viktorovich; Kubankin A. Alexander; Andrґe J.-M. Jean-Michel; Le Guen K. Karine; Jonnard Ph. Philippe; Rossi S. de Sґebastien de; Meltchakov E. Evgueni; Delmotte F. Franck (Poster Session, 2015)
Title screen.